The Impact of Corporate Cultures and Financial Ratios on The Fraudulent Financial Reporting - Prajanto, Agung; Pratiwi, Ririh Dwi (Jurnal Dinamika Akuntansi, 2016)
This study aims to examine and analyze financial statement fraud through financial ratios and corporate culture, case study of companies listed on the Indonesia Stock Exchange Year 2006-2010. The research was conducted at the companies included in the sanctions issued by Capital Markets Supervisory Board (Bapepam) in the period 2006-2010 for companies that committed fraud. While for the companies that did not do fraud, sample was obtained randomly by same asset and industry size. Testing was conducted by using logistic regression to determine the effect of financial ratios and corporate culture on financial statements fraud. Results of research conducted using logistic regression showed that liquidity ratio had positive effect on fraudulent financial statements. While the ratio of gross profit margin and capital turnover indicated a negative impact on financial reporting fraud. Variable of corporate culture was proxied by special relationship transaction, the composition of the founders in board of directors and directors who titled accountant did not effect on fraudulent financial statements.